IMS-based specifications for micro-learning on mobile devices - Pajarito, Karen B.; Feria, Rommel P. (Quezon City College of Engineering, University of the Philippines Diliman, 2016)
The prevalence and continuous advancement of mobile technologies give way to the utilisation of mobile devices for delivering learning content to learners. Education can take advantage of the benefits being provided by mobile devices. Unlike desktop and portable computers, mobile devices have constrained resources that limit its capability to process large learning resources, or learning objects. This provides an opportunity for learners to engage in micro-learning experiences that can take place in seconds up to a few minutes. This research proposes specifications that can be used in the development of micro-learning content for mobile devices. The specifications cover the recommended technical specifications for software for mobile devices and content packaging format of the learning content. A micro-learning platform is presented to prove the applicability of the proposed specifications. The platform provides a web-based authoring tool for the content creators (e.g., teachers) to create micro-learning content, and a mobile application for the learners to access the published learning content.
Thesis (M.S. Computer Science)--University of the Philippines Diliman
Keywords: Mobile communication systems -- Specifications; Mobile communication systems in education; Microlearning